Strategi Komunikasi Menjual Telepon Selular - Donny B. U. (The Winners, 2005)
Article discusses communication strategy that is done by celullar operator in Indonesia. The unique of the communication strategy in celullar phone service business becomes one of key factors, not only in competing market share but also mind share of product user and celullar service that is still in high-tech category.